How many specific B cells are needed to protect against a virus? - Bachmann, M; Kündig, T; Kalberer, C; Hengartner, H; Zinkernagel, R (1994)
The size of the Ab repertoire has been estimated to comprise theoretically somewhere between > 10(10) and approximately 10(4) specificities, dependent on the criteria used. In an attempt to estimate the anti-viral protective Ab repertoire of the mouse the B cell and Ab-forming cell (AFC) frequencies and protective neutralizing Ab levels during the course of an infection with vesicular stomatitis virus (VSV) were analyzed. Determination of AFC frequencies, limiting dilution assays, and adoptive transfer experiments to SCID mice revealed that during the acute phase (day 8) of the immune response, more than 50% of all IgG2a-producing AFCs were specific for VSV, most of them recognizing the neutralizing determinant. In a later phase (days 21 or 50), 10 to 20 times fewer VSV-specific AFCs were present, corresponding to a frequency of approximately 1:10(4) spleen cells. Finally, in a protection assay in SCID mice, adoptively transferred protective Ab concentrations were found to be approximately 1 to 10 micrograms Ab/ml mouse serum. Because during the memory phase of the anti-VSV response usually 10(4) AFC/mouse are engaged to maintain a high level of memory IgG against the neutralizing determinant on VSV and if one assumes a total number of about 10(6) AFCs/mouse, these data suggest a rather limited neutralizing anti-viral protective memory-AFC repertoire of 10(2) to 10(4) different specificities.